Penerapan Teknik Silvikultur Intensif Pada Pengelolaan Hutan Rakyat di Kabupaten Gunungkidul - wiyono wiyono; Puji Lestari; Rochmat Hidayat; Silvi Nur Oktalina; Singgih Utomo; Eko Prasetyo; Agus Ngadianto; Prasetyo Nugroho (Pengabdian dan Pengembangan Masyarakat Sekolah Vokasi UGM, 2018)
The people of Gunungkidul have long experience in rehabilitation program. They manage marginal land be productive community forest. While, the quality of timber from community forest is lower than produced by Perhutani. It is caused the community forest has not been applied intensive silviculture technique. This community engagement program aims to: (1) up grade the farmer knowledge about intensive silviculture technique; (2) rise the farmer awareness for importance of applying intensive silviculture technique; (3) build up the farmer skill to apply intensive silviculture technique; (4) motivate the farmer to produce superior teak seedling and organic fertilizer independently. The target group of this program is the farmer group of Ngudi Makmur at Watusigar Village, Ngawen District, Gunungkidul Regency. This program was held on 2015 to 2016. The methods applied in this program are socialization, field study, training, practice, and technical assistance. The results of this program are demonstration plot of superior teak stand, hedge orchard and nursery of superior teak, and organic fertilizer using Trichoderma sp. This program also succesfull for increase of knowledge, awareness, skills and independence of farmer in applying of intensive silviculture technique.